Optimization of Alkaline Water Production from Rainwater through Electrolysis Method: Effect of Voltage and Time on pH and TDS - Rinda Erliana, Savira; Isnina Noor Ubay; Pangestu, Indra Sakti; Atik, Moh. Umar Dani; Wafa, Almas Diqya (Universitas Negeri Semarang, 2024)
Alkaline water is known to have health benefits due to its higher pH than ordinary water. In this study, the production of alkaline water from rainwater using electrolysis method was optimized, with variations in voltage and time to evaluate its effect on pH and Total Dissolved Solids (TDS). The experiment involved three voltage levels (12 Volt, 24 Volt, and 36 Volt) and three time intervals (10 minutes, 20 minutes, and 30 minutes). The results showed that increasing the voltage and electrolysis time contributed significantly to the increase in water pH, which reached the highest value at 36 Volt for 30 minutes. However, increasing the voltage and time also increased the TDS value linearly, which can affect the water quality if it exceeds a certain limit. This study concludes that the optimal voltage for producing alkaline water with suitable pH and TDS is 24 Volt with an electrolysis time of 20 minutes. Thus, this method offers an efficient and simple solution to produce alkaline water from rainwater, which could potentially benefit public health in areas with limited access to high-quality drinking water.